2007
DOI: 10.1111/j.0014-3820.2001.tb00784.x
|View full text |Cite
|
Sign up to set email alerts
|

The Quantitative Genetics of Fluctuating Asymmetry

Abstract: Fluctuating asymmetry (subtle departures from identical expression of a trait across an axis of symmetry) in many taxa is under stabilizing selection for reduced asymmetry. However, lack of reliable estimates of genetic parameters for asymmetry variation hampers our ability to predict the evolutionary outcome of this selection. Here we report on a study, based on analysis of variation within and between isofemale lines and of generation means (line-cross analysis), designed to dissect in detail the quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 78 publications
4
16
0
2
Order By: Relevance
“…These low values are consistent with the heritability of other morphological asymmetric traits both in man (Bailit et al, 1970) as well as in different animal species (Leamy, 1986(Leamy, , 1997Polak and Starmer, 2001). On the other hand, some studies on man have found significant heritability values of asymmetric traits ranging between 20 and 45% (Livshits and Kobyliansky, 1989;Moller and Thornhill, 1997).…”
Section: Familial Correlation Based On Factorsupporting
confidence: 70%
“…These low values are consistent with the heritability of other morphological asymmetric traits both in man (Bailit et al, 1970) as well as in different animal species (Leamy, 1986(Leamy, , 1997Polak and Starmer, 2001). On the other hand, some studies on man have found significant heritability values of asymmetric traits ranging between 20 and 45% (Livshits and Kobyliansky, 1989;Moller and Thornhill, 1997).…”
Section: Familial Correlation Based On Factorsupporting
confidence: 70%
“…Model fitting is hierarchical, beginning with a simple model, such as the additive model (i.e., the expected mean phenotype of the crosses is a simple linear function of the relative contributions of the parental genomes such that the mean population values of the different crosses fall on a line connecting the two parental means, top graph, Figure 2), and increasing its complexity only if the model fails the joint-scaling test. In the presence of sex-linked effects, the expected mean phenotypic values change (Figure 2), and the line-cross analysis can be expanded to estimate sex-linked, epistatic and maternal effects (e.g., Carbonell et al, 1985;Barbato, 1991;Barbato and Vasilatos-Younken, 1991;Polak and Starmer, 2001;Huttunen and Aspi, 2003).…”
Section: Experimental Protocols: Using Crosses Between Populations Tomentioning
confidence: 99%
“…Adapted from Mather and Jinks (1982, life-history than morphological traits. In addition to those listed in the Appendix, the following papers were used in this analysis: Goud et al (1975), Ketata et al (1975), Arumugam and Muthukrishnan (1979), , Nanda et al (1981Nanda et al ( , 1982, Singh (1981), Bowman and Jones (1984), Singh et al ( , 1984Singh et al ( , 1987Singh et al ( , 1990, Melchinger et al (1986), Randhawa et al (1986), Verma and unus (1986), Garg et al (1987), Pawar et al (1988), Gupta and Labana (1989), Malhotra and Singh (1989), Singh and Nanda (1898), Subbaraman and Sree Rangasamy (1989), Virk et al (1989), Setiamihardja and Knavel (1990), Shinde and Deshmukh (1990), Kishor et al (1992), Wani and Zargar (1992), Ehdaie and Waines (1995), Pooni et al (1994), Tefera and Peat (1997), Ceballos et al (1998), L. L. , Carroll et al (2001), Galloway and Fenster (2001), Gilchrist and Partridge (2001), Khattak et al (2001), Polak and Starmer (2001). For the more specific questions concerning the magnitude of effects we used only six-parameter estimates (i.e., categories 2 and 3).…”
Section: The Databasementioning
confidence: 99%